ANALISIS PENGGUNAAN ALAT BERAT PADA PEKERJAAN TANAH PROYEK PEMBANGUNAN HOTEL MOXY SURAKARTA - Astungkoro, Wisnu Wregas; Nursetyo, Gatot; Arbianto, Reki; Sungkono, Kukuh Kurniawan Dwi (Journal of Civil Engineering and Infrastructure Technology, 2024)
In construction projects, implementation requires heavy equipment to expedite all stages in process. The use of heavy equipment serves to shorten project implementation time and optimize a job. Therefore, the use of heavy equipment in construction projects is expected to accelerate expected work. The use of heavy equipment in construction projects is expected to facilitate existing work and heavy equipment to be used must be selected in an efficient and economical manner. A heavy equipment combination used in earthworks on the Moxy Hotel development project on Jl. Slamet Riyadi, Keprabon, Banjarsari District, Surakarta City is a Kobelco CAT 320D excavator, a Canter 120 Ps dump truck and a Jove JVR 180 D bore machine. The methods used in this research are survey methods and analytical methods. The survey method is used to determine number of heavy equipment in field, heavy equipment type while analytical method is used to determine time heavy equipment is used in the Moxy Hotel Development Project in Surakarta. After an analysis of variations in the duration of heavy equipment that is appropriate and can be used optimally is an alternative because it is more effective and efficient than the calculation of composition analysis and in the field, the time required is also more optimum. With an alternative composition of heavy equipment, namely 1 unit of excavator and 4 units of dump trucks for earthworks, and for foundation drilling work, 2 units of bore machines are needed.